New perspectives on old texts : proceedings of the Tenth International Symposium of the Orion Center for the Study of the Dead Sea Scrolls and Associated Literature, 9-11January, 2005 - Chazon, Esther G.; Amaru, Betsy Halpern.; Clements, Ruth. (Studies on the Texts of the Desert of Judah, 2010)
This volume presents new perspectives on the ancient texts discovered at Qumran. The essays offer fresh insights into particular texts and genres, by applying methods and constructs drawn from other disciplines to the study of the Dead Sea Scrolls, and by exploring new as well as long-standing issues raised by these works. The topics and approaches engaged include group identity, memory, ritual theory, sectarian sociology, philosophy of education, liturgical anthropology, Jewish law, history of religion, and mysticism. The articles in this volume were originally presented at the Tenth Annual International Orion Symposium sponsored in 2005 by the Orion Center for the Study of the Dead Sea Scrolls and Associated Literature at the Hebrew University of Jerusalem.